Determination of optimum insulation thickness using the entransy based thermoeconomic and environmental analysis: a case study for Turkey - Gulten, Ayca (Taylor & Francis Inc, 2020)
In this study, environmental effect of insulation materials while exhibiting the optimum insulation thickness for two different wall types was investigated by thermoeconomic and environmental analysis combined with entransy approach that describes the heat transfer ability of a chosen object. Natural gas was chosen as fuel, while rockwool and glasswool were selected as insulation materials. Two wall types - sandwich and exterior insulated - were evaluated for the calculations in different Turkish cities in Aydin, Mardin, Elazig and Kars provinces. Firstly entransy based environmental and thermoeconomic analysis were conducted and optimum insulation thicknesses were calculated. Then, entransy based cost savings, values for combustion parameters and environmental impacts were presented for different wall types, insulation materials, and cities. Based on thermoeconomic method combined with entransy approach, insulation thickness varied between 0.0615 and 0.0001 m for exterior insulated walls while it varied between 0.0530 and 0.0027 m for the sandwich wall model. Entransy based environmental thickness varied between 0.021 and 0.0174 m and presented higher values compared to thermoeconomic results. It was found that thermoeconomic insulation thickness provided better energy and cost savings while environmental results aimed to preserve the earth with lower fuel consumption and CO2 emissions.
Keywords: Optimum insulation thickness; entransy; environmental effect; insulation materials; energy saving